2023
DOI: 10.3390/molecules28135025
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and Evaluation of Secondary Metabolites from Trichoderma harzianum: GC-MS Analysis, Phytochemical Profiling, Antifungal and Antioxidant Activity Assessment

Wassima Lakhdari,
Ibtissem Benyahia,
Mustapha Mounir Bouhenna
et al.

Abstract: In this study, we investigated in vitro the potential of Trichoderma harzianum to produce bioactive secondary metabolites that can be used as alternatives to synthetic compounds. The study focused on analyzing two extracts of T. harzianum using ethyl acetate and n-butanol solvents with different polarities. The extracts were examined using phytochemical analysis to determine the content of polyphenols, flavonoids, tannins, and alkaloids. Thin-layer chromatography (TLC) and Gas chromatography-mass spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…The development of Colletotrichum gloeosporioides and A. alternata is inhibited by the T. koningiopsis T2 strain through the production of metabolites derived from VOCs and non-VOCs 110 . The presence of bioactive chemicals in the extract suggests that the VOCs emitted by T. harzianum have a significant role as both an antioxidant and an antifungal agent, as indicated by Lakhdari et al 111 .…”
Section: Discussionmentioning
confidence: 89%
“…The development of Colletotrichum gloeosporioides and A. alternata is inhibited by the T. koningiopsis T2 strain through the production of metabolites derived from VOCs and non-VOCs 110 . The presence of bioactive chemicals in the extract suggests that the VOCs emitted by T. harzianum have a significant role as both an antioxidant and an antifungal agent, as indicated by Lakhdari et al 111 .…”
Section: Discussionmentioning
confidence: 89%
“…Studies have shown that T. harzianum contains lactone (Lakhdari et al 2023;Xiao et al 2023). Lactone substances can stop bacteria from growing and lessen oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…GC-MS analysis showed that biocontrol agents like Trichoderma produced various volatile organic compounds (VOCs), including alcohols, acids, esters, sesquiterpenes, and ketones. These compounds provide specific benefits in various biological mechanisms, like competition, symbiosis, metal transportation, growth differentiation, signaling, and mycoparasitic behavior [55], and also show antifungal and antibacterial activities against various phytopathogens like Fusarium spp. and Sclerotium spp.…”
Section: Gcms Analysismentioning
confidence: 99%